Changes and transformations of the international system in the 21st century: a new era in global relations? - Artavia-Medrano, Argentina (2025)
The 21st century has witnessed a profound transformation of the international system, marked by the emergence of new actors, the reconfiguration of power, the intensification of global challenges and the crisis of international institutions. Globalization, the technological revolution, multipolarity and transnational threats have generated a scenario characterized by unprecedented complexity, which challenges traditional notions of sovereignty, security and governance. In this context, it is essential to analyze the main dynamics that shape contemporary international politics and impose the aforementioned challenges to traditional power structures, as well as to reflect on the implications and possible scenarios of this ever-changing system. Analyzing the main transformations of the international system, their causes and implications, and the challenges facing both States and international actors in this new era is an imperative for the discipline of International Relations, academia and society as a whole. This new issue of the Revista de Relaciones Internacionales aims to contribute to this purpose by offering various articles that contribute to the theoretical discussion and knowledge of the international reality; it assumes with scientific rigor the responsibility of opening spaces for the academic community and the society to which it is owed.